2018
DOI: 10.1080/23322039.2018.1558713
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of working capital requirement in listed firms: Empirical evidence using a dynamic system GMM

Abstract: Working capital management is a critical element in the survival of every firm. While the effective management of working capital leads to value creation in firms, ineffective management of working capital, on the other hand, does not only destroy value but can lead to the eventual solvency of the firm. The search for the factors that influence working capital management has, therefore, become a worthwhile exercise embarked upon by both managers and scholars. The main aim of this study is thus to empirically i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 32 publications
5
45
0
4
Order By: Relevance
“…However, they agreed that their results might vary when the leverage level of a firm changes. Nyeadi and Sare [37] reported that different leverage levels significantly affect profit. Firms with high leverage suffer from the higher cost of short-term debt [22,24].…”
Section: Wcf and Profitability Under The Moderating Role Of Leveragementioning
confidence: 99%
See 1 more Smart Citation
“…However, they agreed that their results might vary when the leverage level of a firm changes. Nyeadi and Sare [37] reported that different leverage levels significantly affect profit. Firms with high leverage suffer from the higher cost of short-term debt [22,24].…”
Section: Wcf and Profitability Under The Moderating Role Of Leveragementioning
confidence: 99%
“…Such firms mostly use internal sources to repay debt and have to rely on external debt for working capital [4]. Lenders have severe liquidity concerns with high-leverage firms because a significant portion of liquid assets is required to pay back debt charges [37]. High-leverage firms already suffer from heavy debt load and lenders are not willing to provide further loans with normal interest rates, so these firms have to pay premium interest rates on further debt.…”
Section: Wcf and Profitability Under The Moderating Role Of Leveragementioning
confidence: 99%
“…Exchange rates directly affect their financial outcome as companies import their inputs or sell their trading inventory on the international market, resulting in a direct competitive impact on domestic and international markets. Falls in demand for foreign trade (Oseifuah, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Biaya agensi akan berkurang seiring dengan penurunan penggunaan utang dan risiko kebangkrutan (Jensen, 1986). Biaya agensi mengurangi konflik kepentingan antara manajemen dan pemegang saham dengan mengurangi penggunaan utang, sehingga mengurangi risiko gagal bayar (Nyeadi et al, 2017).…”
Section: Karakteristik Perusahaan Dan Struktur Modalunclassified